The Effect of A Sports Recreation Programme To Reduce Negative Thinking Among Second Grade Middle School Students In East Baghdad Suburbs - Ikhlas Sabah Ali Al-Ghazi (Indonesian Journal Publisher, 2025)
The research aims to design a sports recreation programme to reduce negative thinking among second grade intermediate students of East Baghdad suburban schools, and to identify the effect of the sports recreation programme in reducing negative thinking among the research sample.To achieve the goal, the researcher used the experimental method and the design of the experimental and control groups with pre-testing and post-testing to suit it with the research issue and objectives, the research population included intermediate second grade students with ages (14_15) years in East Baghdad suburbs education for the academic year (2024-2025), and the sample was selected 2025), and the research sample was selected by the purposive method, and they are the students of the second intermediate grade of Martyr Hussein Karidi Intermediate and their number (320) students divided into (8) divisions, namely (A, B, C, D, E, F, G, H) and they were divided into two experimental and control groups and were selected by random method (lottery), as the experimental group was identified from division (C) and their number (32), which was trained on the recreational programme, and the control group from division (E) and their number (35), which used the traditional curriculum followed by the teacher of education in the outskirts of East Baghdad for the academic year (2024-2025), and the experimental and control groups were divided into two experimental and control groups. The researcher conducted the pre-test and post-test for the experimental and control groups, and conducted the appropriate statistical treatments, and the researcher concluded that the negative thinking scale is able to detect negative thinking in the second intermediate grade students in East Baghdad suburbs education, and that the sports recreational programme has a clear effect on reducing negative thinking in the second intermediate grade students in East Baghdad suburbs education.The researcher recommends that the proposed recreational sports programme should be used in middle schools because the middle stage represents the stage of early and middle adolescence in which biological, psychological and social changes occur, the possibility of using the negative thinking scale to measure the level of negative thinking among students aged 14-15 years to identify their reality, the media to increase the awareness of parents and teachers in treating their children well and urging them to cooperate with others and take into account the circumstances of the stage he is going through to try to reduce negative thinking.